Prevalence of clinically significant Hepatopulmonary Syndrome among Patients with Chronic Liver Disease and Portal Hypertension - Almohana, Sadiq (AL-Kindy College Medical Journal, 2011)
Background : The hepatopulmonary syndrome (HPS) is defined as the triad of liver disease, arterial deoxygenation, and pulmonary vascular dilatation. The reported prevalence of HPS in cirrhotic patients varies between 5% -17.5%.Objective : To estimate the prevalence of hepatopulmonary syndrome among patients with chronic liver disease and portal hypertension and to study the correlation between HPS and the severity of liver disease.Patients and methods : Thirty patients were studied for the presence of HPS using transthoracic contrast echocardiography for detection of pulmonary vasodilatation. Arterial oxygen saturation (SaO2) was determined in erect and supine position using a pulse oximeter , (SaO2 ≤ 92 % in supine position and/or a decrease of ≥ 4% after change from supine to upright position) to detect hypoxia and ortheodeoxia.Result : Eleven of thirty patients (36.6%) with chronic liver disease and portal hypertension were found to have contrast echocardiographic evidence of intrapulmonary right-to-left shunting. Arterial oxygen desaturation was present in 3 patients (27.3%) of those with intra-pulmonary right-to-left shunting ,they were considered as clinically significant HPS ,the remaining 8 patients were considered as subclinical HPS. Dyspnoea was more often present in patients with clinically significant HPS (100%) compared with subclinical HPS (25%), and patients without HPS (9%). HPS correlated significantly with severity of liver disease according to the Child-Pugh score.Conclusion: hepatopulmonary syndrome is not uncommon , the prevalence of clinically significant hepatopulmonary syndrome (in this study) was 10% of patients with chronic liver disease and it correlated with disease severity according to the Child-Pugh score